Optimizing Production Efficiency Through Time Study in UPS Manufacturing - Dhamodharan S,; Lourdu Roshan A,; Dr. S. Krishnakumari, (International Journal of Scientific Research in Science and Technology, 2024)
Time studies have long been a proven method for improving operational efficiency, particularly in complex manufacturing environments like Uninterruptible Power Supply (UPS) production. By analyzing how tasks are performed and identifying opportunities for optimization, time studies help companies improve productivity, reduce costs, and ensure quality consistency. This article delves into how time studies can be implemented in UPS manufacturing, the benefits they bring, and the challenges that must be addressed.
Keywords: Uninterruptible Power Supply; Productivity; Quality Consistency; UPS Manufacturing; Production Efficiency